A Review: Gaseous Interventions for Listeria monocytogenes Control in Fresh Apple Cold Storage - Guan, Jiewen; Lacombe, Alison; Rane, Bhargavi; Tang, Juming; Sablani, Shyam; Wu, Vivian C. H. (Frontiers in Microbiology, 2021)
Listeria monocytogenes (L. monocytogenes) causes an estimated 1600 foodborne illnesses and 260 death yearly. These outbreaks are a major concern for the apple industry since fresh produce cannot be treated with thermal technologies for pathogen control before human consumption. Recent caramel apple outbreaks indicate that the current non-thermal sanitizing protocol may not be sufficient for pathogen decontamination. Federal regulations provide guidance to apple processors for sanitizer residue limits, organic production, and good manufacturing practices (GMPs). However, optimal methods to control L. monocytogenes on fresh apples still need to be determined. This review discusses L. monocytogenes outbreaks associated with caramel apples and the pathogen’s persistence in the environment. In addition, this review identifies and analyzes possible sources of contaminant for the apples during cold storage and packing. Gaseous interventions are evaluated for their feasibility for L. monocytogenes decontamination on apples in this review. For example, apple cold storage, which requires waterless interventions, may benefit from gaseous antimicrobials like chlorine dioxide (ClO2) and ozone (O3). In order to reduce the contamination risk during cold storage, significant research is still greatly needed to develop effective methods to reduce microbial loads on fresh apples. This requires commercial-scale validation of gaseous interventions and intervention integration to the current existing apple cold storage. Additionally, the impact of the interventions on final apple quality should be taken into consideration. Therefore, this review intends to provide apple industry suggestions to minimize the contamination risk of L. monocytogenes during cold storage and hence prevent outbreaks and reduce economic losses.